2021
DOI: 10.1007/978-3-030-82095-4_5
|View full text |Cite
|
Sign up to set email alerts
|

Study of Sustainable Transport Enhancements Through Analysing Utilisation Levels of Rail Lines with Enhanced Passenger and Freight Services: A Case Study on a Local Rail Line Through Simulation Modelling and Scenarios

Abstract: Due to climate change, more sustainable passenger and freight transport is in need. Rail is considered a more sustainable mode of transport compared to others such as road transport. Usage of rail lines that are currently under-utilised could help increase the sustainability of transport through enhanced utilisation of them. This study looks at the Marston Vale Line, identifying it as under-utilised, and through the use of event-based simulation modelling, observes the current utilisation level and develops wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The use of the SIMUL8 software modelling package for rail operations and management-focused research has been demonstrated in various studies [3,12,13,23,24,31]. The software allows for both analysis of the queuing system and examination of the passenger behaviour in interactions with ticket facilities.…”
Section: Simul8 and Considerations Before Building The Simulation Modelmentioning
confidence: 99%
“…The use of the SIMUL8 software modelling package for rail operations and management-focused research has been demonstrated in various studies [3,12,13,23,24,31]. The software allows for both analysis of the queuing system and examination of the passenger behaviour in interactions with ticket facilities.…”
Section: Simul8 and Considerations Before Building The Simulation Modelmentioning
confidence: 99%